2001
DOI: 10.1159/000054633
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens Act in Rat Hippocampus and Frontal Cortex to Produce Rapid, Receptor-Mediated Decreases in Serotonin 5-HT<sub>1A</sub> Receptor Function

Abstract: Previously our laboratory has shown that 17β-estradiol in vivo rapidly decreases R(+)-8-OH-DPAT-stimulated [35S]GTPγS binding (a measure of the initial biochemical event in the intracellular signaling pathway associated with 5-HT1A receptors) in the hippocampus, frontal cortex and amygdala. Studies were designed to determine if 17β-estradiol also acts in vitro on estrogen receptors in the hippocampus and frontal cortex to decrease 5-HT1A receptor function. Hippocampus and front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 23 publications
(34 reference statements)
1
32
0
1
Order By: Relevance
“…The most likely mechanism responsible for the observed PPI effects is that estrogen treatment altered signalling of the 5-HT 1A receptor. Acute estrogen treatment in ovariectomized rats desensitized 5-HT 1A receptor function, as indicated by a reduction in [ 35 S]GTPgS binding (Mize and Alper, 2000;Mize et al, 2001). Further studies are required to investigate if similar mechanisms occur in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely mechanism responsible for the observed PPI effects is that estrogen treatment altered signalling of the 5-HT 1A receptor. Acute estrogen treatment in ovariectomized rats desensitized 5-HT 1A receptor function, as indicated by a reduction in [ 35 S]GTPgS binding (Mize and Alper, 2000;Mize et al, 2001). Further studies are required to investigate if similar mechanisms occur in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that the 5-HT 1A receptor subtype is a mediator of the antidepressant-like action of E 2 . Evidences in favor of this hypothesis are the results derived from in vitro and in vivo studies, showing that the 5-HT 1A receptor subtype is a target of estrogens and some estrogen-like compounds (Bethea et al, 1998;Biegon et al, 1983;Mize and Alper, 2000;Mize et al, 2001;Raap et al, 2000;Uphouse, 2000). Indeed, Lu and Bethea (2002) demonstrated that E 2 induces the desensitization of 5-HT 1A receptors in the DRN of monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that in vitro, 17β-estradiol and diethylstilbestrol decrease 5-HT 1A receptor coupling to Gα in rat hippocampus and frontal cortex [13]. In addition, we demonstrated that the effects of 17β-estradiol are potently and completely blocked by the estrogen receptor antagonist ICI 182,780.…”
Section: Introductionmentioning
confidence: 85%
“…A piece of tissue was placed into one well of a 6-well cell culture plate along with 10 ml of HEPES buffer containing vehicle, 17β-estradiol or related compound. The plates were transferred to a water bath (37°C) under continuous aeration [13]. In studies involving estrogen receptor antagonists or protein kinase inhibitors, a 15-min preincubation in the presence of the inhibitor was performed prior to the addition of 17β-estradiol.…”
Section: Methodsmentioning
confidence: 99%